2007
DOI: 10.1002/ajpa.20548
|View full text |Cite
|
Sign up to set email alerts
|

Human dental microwear from Ohalo II (22,500–23,500 cal BP), southern Levant

Abstract: Dietary hardness and abrasiveness are inferred from human dental microwear at Ohalo II, a late Upper Palaeolithic site (22,500-23,500 cal BP) in the southern Levant. Casts of molar grinding facets from two human skeletons were examined with a scanning electron microscope. The size and frequency of microwear was measured, counted, and compared to four prehistoric human groups from successive chronological periods in the same region: pre-pottery Neolithic A, Chalcolithic (this study); Natufian, pre-pottery Neoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(12 citation statements)
references
References 70 publications
2
6
0
Order By: Relevance
“…The results of previous analyses and the present study indicate that there may be variable interaction effects of age and tooth loss on mandibular ramus morphology in terms of differential dietary regimes, as modern samples generally have lower masticatory loads than archaeological skeletal samples (Bigoni, Krajíček, Sládek, Velemínský, & Velemínská, ; Mahoney, ; Watson, ). With regard to food quality, different food preparation techniques can affect the stiffness or coarseness of food and, in turn, affect cranial and mandibular morphology (Bigoni, Krajíček, Sládek, Velemínský, & Velemínská, ; Mahoney, ; Watson, ). For instance, Bigoni, Krajíček, Sládek, Velemínský, and Velemínská () showed that facial bilateral asymmetry was higher in a high socio‐economic skeletal sample from an early medieval central European site than low socio‐economic modern samples.…”
Section: Discussionsupporting
confidence: 47%
“…The results of previous analyses and the present study indicate that there may be variable interaction effects of age and tooth loss on mandibular ramus morphology in terms of differential dietary regimes, as modern samples generally have lower masticatory loads than archaeological skeletal samples (Bigoni, Krajíček, Sládek, Velemínský, & Velemínská, ; Mahoney, ; Watson, ). With regard to food quality, different food preparation techniques can affect the stiffness or coarseness of food and, in turn, affect cranial and mandibular morphology (Bigoni, Krajíček, Sládek, Velemínský, & Velemínská, ; Mahoney, ; Watson, ). For instance, Bigoni, Krajíček, Sládek, Velemínský, and Velemínská () showed that facial bilateral asymmetry was higher in a high socio‐economic skeletal sample from an early medieval central European site than low socio‐economic modern samples.…”
Section: Discussionsupporting
confidence: 47%
“…Each molar was replicated prior to removal for sectioning, and an epoxy cast was prepared (e.g., Mahoney, 2007). Contaminants were removed from the enamel surface of each molar using ethanol and cotton wool.…”
Section: Sample Preparationmentioning
confidence: 99%
“…In archaeology, dental microwear has been used to examine the impact of the transition from foraging to agriculture on human diet (e.g., Hogue and Melsheimer, 2008), also in the Levant (Mahoney, 2006a(Mahoney, , 2007 and North Mesopotamia (Molleson and Jones, 1991). Several papers have been published about dietary transitions in prehistorical and historical periods, especially in North America (e.g., Schmidt, 2001;Organ et al, 2005;Ma and Teaford, 2010).…”
Section: Introductionmentioning
confidence: 98%
“…Usually good quality replicas of selected tooth facets (primarily in molars) are imaged using scanning electron microscopy (SEM), 300Â or 500Â magnification (Galbany et al, 2004;Mahoney, 2007). Phase II facets or buccal crown side allow better distinction between diets than Phase I facets (Krueger et al, 2008).…”
Section: Introductionmentioning
confidence: 99%